Scaling Conversations - MacLeod, Dave (Ascent Audio, 2021)
Find out what your customers and employees are really thinking with this indispensable resource Scaling Conversations: How Leaders Access the Full Potential of People delivers invaluable strategies for how leaders can make their communications more inclusive and access the voices of those employees who rarely feel empowered to speak up. As constituent numbers scale, leaders have traditionally struggled to make communications a conversation with the entire organization, settling instead for small focus groups, talking at people in town halls, and delivering surveys after the fact. The result is exclusive, narrow decision-making that disengages and under-utilizes talent and human capital. And now, as the remote environment grows, the challenge and imperative for engaging conversations on a wider scale is even greater. Scaling Conversations provides the solution. Having led a remote team for over a decade and having worked with thousands of leaders across North America, Dave MacLeod teaches you how to: scale your business by listening to the voices that really matter; access and maximize the human capital in your organization; make decisions that create unity and move the group forward; and decrease employee turnover caused by poor communication.